Path Planning Algorithm for Mobile Robots - Jian, Hanwen (Transactions on Computer Science and Intelligent Systems Research, 2024)
Path planning algorithm is a critical technology enabling mobile robots to realize autonomous navigation. In this paper, the path-planning technology of mobile robots is deeply discussed, and the operation mechanism and principle of different algorithms are analyzed in detail. Based on the understanding of the characteristics of mobile robot path planning algorithms, these algorithms are divided into three categories: traditional planning algorithm, intelligent planning algorithm, and sampling-based planning algorithm. This paper reviews and discusses the key research results in recent years, especially the advantages and limitations of various algorithms, which are analyzed in depth. Considering the current research status of mobile robot path planning technology, this paper also forecasts future research trends to provide new thinking direction for further development, such as the mixed-use of different types of path planning algorithms, the adoption of new technologies such as deep learning for path planning, and the application of multi-robot collaborative path planning.